Structural and Stratigraphic Studies of the Northern Ellesmere Ice Shelf - Marshall, Ernest W. (ARCTIC, 1955)
Report complementary to Hattersley-Smith and others' (AB. No 40304). Ice cores obtained near Ward Hunt Island (83 05 N, 75 W) and on trips along the coast showed four ice types composing the shelf: iced firn, glacier, lake, and sea ice. The thick primary portion of the shelf seems to be composed stratigraphically of three major ice units. The uppermost consisting of granular iced firn untouched by sea water, with associated lenses of lake ice, is separated by a dirt layer from the middle unit, similarly composed but soaked by migrating sea water. Evidence indicates the lowest unit to be glacier ice (or sea ice interfingered with glacier or lake ice) upon which the iced firn accumulates. The process is briefly described.